Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
x² - 6x - 27 = 0
x = -(-6) +/- √((-6)² - 4(1)(-27))
2(1)
x = 6 +/- √(36 + 108)
2
x = 6 +/- √(144)
2
x = 6 +/- 12
2
x = 3 + 6
x = 3 + 6 x = 3 - 6
x = 9 x = -3
x = -(-6) +/- √((-6)² - 4(1)(-27))
2(1)
x = 6 +/- √(36 + 108)
2
x = 6 +/- √(144)
2
x = 6 +/- 12
2
x = 3 + 6
x = 3 + 6 x = 3 - 6
x = 9 x = -3
The quadratic equation x² - 6x - 27 = 0 is equivalent to (x - 3)² = 36. Then the correct option is C.
What is a quadratic equation?
It's a polynomial with a value of zero. There exist polynomials of variable power 2, 1, and 0 terms. A quadratic equation is an equation with one statement in which the degree of the parameter is a maximum of 2.
The quadratic equation is given below.
x² - 6x - 27 = 0
The quadratic equation can be written as
Add 9 on both sides, then we have
x² - 6x + 9 = 9 + 27
(x - 3)² = 36
More about the quadratic equation link is given below.
https://brainly.com/question/2263981
#SPJ2
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.